Effects of Dexamethasone on Hepatic Ischemia-reperfusion Injuries - Vahid Akbari Kordkheyli; Setareh Zarpou; Pooneh yazdani; Abbas Khonakdar Tarsi (Journal of Mazandaran University of Medical Sciences, 2017)
Ischemia-reperfusion injuries (IRI) are the major causes of liver failure after various types of liver surgeries such as biopsy, transplantation, and tumor surgery. Its pathogenesis is multifactorial and complex that involves ATP depletion, hepatocyte edema, acidosis, oxidative stress, inflammation, and microcirculation defect which can eventually progress to liver cell death, systemic inflammatory response syndrome (SIRS), multiple organ dysfunction syndrome, and even acute graft rejection. There are much evidences that suggest applying anti-inflammatory drugs could be a proper strategy to decrease IRI. Dexamethasone is a highly potent synthetic corticosteroid that its beneficial effects on various tissues in IRI are well documented. It also suppresses inflammation and immune response in different pathologic conditions. Its functional mechanism is different in various types of cells and involves: inactivation of NF-κB and AP-1, inhibition of releasing PLA2 and arachidonic acid, and induction of ERK1/2 and SGK-1. By these processes dexamethasone is able to prevent cytokine overproduction and leukocyte activation, recruitment and infiltration. In this review, we aimed to explain the protective effects of dexamethasone on liver ischemia-reperfusion injuries.